Patterns of participation over four rounds of annual fecal immunochemical test-based screening for colorectal cancer: what predicts rescreening? - Joanne M. Osborne; Carlene Wilson; Amy Duncan; Stephen R. Cole; Ingrid Flight; Deborah Turnbull; Donna L. Hughes; Graeme P. Young (BMC, 2017)
Abstract Background Participation at the recommended intervals is critical for screening to be effective in reducing colorectal cancer (CRC) incidence. This study describes patterns of screening participation over four rounds of fecal immunochemical testing (FIT) to identify whether demographic variables and prior screening satisfaction are significantly associated with patterns of re-participation. Methods Baseline surveys were mailed to 4000 South Australians randomly selected from the electoral-roll. Respondents (n = 1928/48.2%) were offered four annual FIT rounds. Screening participation and satisfaction at each round were recorded. Results Study participation was 58.5, 66.9, 73.1 and 71.4% respectively over four rounds. Three participation patterns were described: consistent participation (43.1%), consistent non-participation (26.4%) and inconsistent participation (changeable; 30.5%), including intermittent and sustained change patterns. Sustained change described those who changed participatory behavior and then maintained for at least two rounds (n = 375/19.5%). Older people, and those not working were most likely to sustain participation. Younger invitees, especially men, were more likely to change participatory behavior and sustain the change. People with higher disadvantage, less education, not working and with no prior (pre-trial) screening experience were more likely to start participating and drop out. People dissatisfied with a prior screening test, including finding aspects embarrassing or unpleasant, were also more likely not to participate in annual screening or to drop out. Conclusions The findings identify those at risk of non- or inconsistent participation in rescreening. They should aid targeting of interventions for demographic groups at risk and ensuring screening experiences are not perceived as unpleasant or difficult.